Advances in traumatic brain injury research in 2020: A review article - Revanth Goda; P Sarat Chandra (Apollo Medicine)
Perhaps in no other area of neurosurgery, has a greater research been done as in traumatic brain injury (TBI). Despite this, TBI remains one of the biggest killers around the world and especially in India. Decompressive craniotomy still remains one of the mainstay paradigms in the management of TBI. The following article explores several new modalities of treatment, and these include the role of beta-blockers for TBI, updates on decompressive craniotomy, the results of DECRA and RESCUEicp trials, diagnostic and prognostic biomarkers in TBI, vascular dysfunction, neuroimaging, and role of neuroinflammation in TBI.